Unusual presentation of a cutaneous metastasis in the face arising from gastric cancer: a case report. (September 2018) - Kirchberger, Michael Constantin
A well-known example of gastrointestinal cancers metastasizing to the skin is Sister Mary Joseph's nodule, which usually presents as a cutaneous nodule on the umbilicus. In this case, a 91-year-old man was referred to our dermatology clinic for a rapidly growing 3 cm × 2 cm ulcerative nodule at his chin. Biopsy showed skin metastasis originating from a gastric adenocarcinoma. The subcutaneous and cutaneous manifestation of gastric cancer is very rare and associated with a poor prognosis and widespread metastatic disease as presented in this case. However, skin metastasis may be the first clinically apparent sign of underlying systemic malignancy and therefore immediate clarification in case of uncertainty is recommended.